The utility of cardiac magnetic resonance imaging in the diagnosis of adult patients with acute myocarditis: a systematic review and meta-analysis. (15th September 2022) - Khanna, Shaun; Amarasekera, Anjalee T.; Li, Cindy; Bhat, Aditya; Chen, Henry H.L.; Gan, Gary C.H.; Ugander, Martin; Tan, Timothy C.
Abstract: Background: The presence of myocardial late gadolinium enhancement (LGE) indicates myocyte necrosis, and assists with the diagnosis of acute myocarditis (AM). Cardiac magnetic resonance (CMR) measures other than LGE i.e. tissue characterization and myocardial structural and functional parameters, play an important diagnostic role in assessment for inflammation, as seen in AM. The aim of this systematic review was to appraise the evidence for the use of quantitative CMR measures to identify myocardial inflammation in order to diagnose AM in adult patients. Methods: A systematic literature search of medical databases was performed using PRISMA principles to identify relevant CMR studies on AM in adults (2005-2020; English; PROSPERO registration CRD42020180605). Data for a range of quantitative CMR measures were extracted. Continuous variables with low heterogeneity were meta-analyzed using a random-effects model for overall effect size measured as the standard mean difference (SMD). Results: Available data from 25 studies reporting continuous quantitative 1.5-T CMR measures revealed that AM is most reliably differentiated from healthy controls using T1 mapping (SMD 1.80, p <0.01) and T2 mapping (SMD 1.63, p <0.01), respectively. All other measures examined including T2-weighted ratio, extracellular volume, early gadolinium enhancement ratio, right ventricular ejection fraction, and LV end-diastolic volume, mass, ejection fraction, longitudinal strain, circumferential strain, and radial strain also had discriminatory ability although with smaller standard mean difference values (|SMD| 0.32–0.96, p < 0.01 for all). Conclusions: Meta-analysis shows that myocardial tissue characterization (T1 mapping>T2 mapping) followed by measures of left ventricular structure and function demonstrate diagnostic discriminatory ability in AM. Highlights: Myocardial structure, function and tissue characterization on cardiac magnetic resonance (CMR) plays an important diagnostic role in assessment of inflammation. This meta-analysis demonstrated that beyond late gadolinium enhancement, acute myocarditis is most reliably differentiated from healthy controls using T1 and T2 mapping (greatest overall effect sizes). CMR measures of extra-cellular volume, right ventricular ejection fraction, early gadolinium enhancement ratio and left ventricular volume, ejection fraction & strain all demonstrated smaller effect sizes, compared to T1 and T2 mapping.